2002
DOI: 10.1123/japa.10.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Self-Schemata and Exercise Identity in Older Adults

Abstract: One's sense of self over time, or identity, is an important component of well-being. Schemata formed from components of identity, such as an exerciser schema, have been associated with behaviors that promote physical activity. This study explored the process of exercise-identity formation in active older adults, questioned whether or not the term exerciser was a meaningful descriptor for their behavior, and examined whether self-views were mediated by perceptions of aging. Thirteen older adults (66–90 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 0 publications
1
33
1
Order By: Relevance
“…There was one case study with a single participant (Roper, Molnar, & Wrisberg, 2003); nine studies had more than one but fewer than 50 participants (Dionigi, 2006b;Dionigi, Horton, & Baker, 2013a, 2013bDionigi, Horton, & Bellamy, 2011;Grant, 2001; Leavy & Aberg, 2010;Stathi, Fox, & McKenna, 2002;Whaley & Ebbeck, 2002;Wing, 2008); and three studies had over 100 participants (Dionigi, 2002a(Dionigi, , 2002bDionigi & O'Flynn, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was one case study with a single participant (Roper, Molnar, & Wrisberg, 2003); nine studies had more than one but fewer than 50 participants (Dionigi, 2006b;Dionigi, Horton, & Baker, 2013a, 2013bDionigi, Horton, & Bellamy, 2011;Grant, 2001; Leavy & Aberg, 2010;Stathi, Fox, & McKenna, 2002;Whaley & Ebbeck, 2002;Wing, 2008); and three studies had over 100 participants (Dionigi, 2002a(Dionigi, , 2002bDionigi & O'Flynn, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…As Dionigi, Horton, and Baker (2013b) suggest, an identity constructed on physically capability, may be maladaptive when faced with inevitable physical decline. It is however important to note that the strength of this finding is questionable, as not all studies addressed the concept of self-identity and in those that did one exercise study found conflicting results which suggest that some physically active older adults search for broader descriptions of self (Whaley & Ebbeck, 2002).Resistance to dominant negative stereotypes also appears to be consistent across groups. Paradoxically, in resisting negative stereotypes there is also a tendency to reproduce PSYCHOSOCIAL WELLBEING 18 these same stereotypes as part of the differentiation process.…”
mentioning
confidence: 86%
See 3 more Smart Citations